T Cells in Preterm Infants and the Influence of Milk Diet - Sproat, Thomas; Payne, Rebecca Pamela; Embleton, Nicholas D.; Berrington, Janet; Hambleton, Sophie (Frontiers in Immunology, 2020)
Preterm infants born before 32 weeks gestational age (GA) have high rates of late onset sepsis (LOS) and necrotizing enterocolitis (NEC) despite recent improvements in infection control and nutrition. Breast milk has a clear protective effect against both these outcomes likely due to multiple mechanism which are not fully understood but may involve effects on both the infant’s immune system and the developing gut microbiota. Congregating at the interface between the mucosal barrier and the microbiota, innate and adaptive T lymphocytes (T cells) participate in this interaction but few studies have explored their development after preterm delivery. We conducted a literature review of T cell development that focuses on fetal development, postnatal maturation and the influence of milk diet. The majority of circulating T cells in the preterm infant display a naïve phenotype but are still able to initiate functional responses similar to those seen in term infants. T cells from preterm infants display a skew towards a T-helper 2(Th2) phenotype and have an increased population of regulatory cells (Tregs). There are significant gaps in knowledge in this area, particularly in regards to innate-like T cells, but work is emerging: transcriptomics and mass cytometry are currently being used to map out T cell development, whilst microbiomic approaches may help improve understanding of events at mucosal surfaces. A rapid rise in organoid models will allow robust exploration of host-microbe interactions and may support the development of interventions that modulate T-cell responses for improved infant health.